Synchronized scheduling model for container terminals using simulated double-cycling strategy. (April 2021) - Ahmed, Essmeil; El-Abbasy, Mohammed S.; Zayed, Tarek; Alfalah, Ghasan; Alkass, Sabah
Highlights: A double-cycling strategy for handling containers in sea terminals is proposed. The strategy aims to minimize the vessel turnaround time and handling costs. Synchronized scheduling models using simulation were developed. The models consider the uncertainties in the work tasks durations. Results showed significant improvements by employing the double-cycling strategy. Abstract: Global ocean-based trade has been increasing significantly. To keep pace with this growth, a new generation of large vessels has been introduced to maximize shipping productivity. The primary goal of container terminals is to accelerate vessel turnaround time through effective coordination of the main handling components. This study proposes an efficient strategy to handle containers by employing double-cycling to minimize the number of empty travel trips of yard trucks. To verify the efficiency of the proposed strategy, two simulation models were developed and implemented based on a real-life case study considering uncertainties in the work task duration. The integrated single-cycling model predicted productivity with an accuracy rate of over 97%, compared with the actual site productivity. When compared to the standard single-cycling model, the double-cycling model enhanced productivity and reduced vessel turnaround time by up to 62% and 38%, respectively, and achieved cost savings of up to 27%.